The meaning of self-acceptance in the dynamics of families with children with special needs - Nilam Nisa; Siti Jaro'ah; Fitrania Magfiroh (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
This study examines the process of self-acceptance in families of children with special needs (CSN) as a complex and dynamic psychological phenomenon. The aim of this study is to understand how families interpret their emotional experiences, as well as the factors that influence the acceptance process in the context of everyday life. The participants consisted of three family members who are directly involved in the care of children with special needs and have been aware of the child’s condition for at least two years. This study employed a qualitative approach using Interpretative Phenomenological Analysis (IPA). Data were collected through semi-structured interviews and participatory observation, and subsequently analyzed using thematic analysis. The findings indicate that the process of self-acceptance involves emotional stages of denial, anger, bargaining, depression, and acceptance. However, these stages do not occur in a linear or sequential manner; rather, they are fluctuating and recurring. The acceptance process is not only experienced at the individual level but also occurs collectively within the family system. Internal factors such as emotional regulation and religiosity, as well as external factors including social support, community, and environmental influences, play a significant role in shaping adaptive coping and family resilience. The findings further emphasize that self-acceptance is an ongoing process of meaning-making rather than merely the final outcome of emotional adaptation. The implication is that psychosocial interventions should be designed comprehensively by involving all family members and strengthening social support to enhance the psychological well-being of families in a sustainable manner.